2012
DOI: 10.1103/physrevb.85.094519
|View full text |Cite
|
Sign up to set email alerts
|

Distinct oxygen hole doping in different layers ofSr2CuO4δ/La2CuO4superlattices

Abstract: X-ray absorption in Sr2CuO 4−δ −La2CuO4 (SCO-LCO) superlattices shows a variable occupation with doping of a hole state different from holes doped for x x optimal in bulk La2−xSrxCuO4 and suggests that this hole state is on apical oxygen atoms and polarized in the a − b plane. Considering the surface reflectivity gives a good qualitative description of the line shapes of resonant soft X-ray scattering. The interference between superlattice and surface reflections was used to distinguish between scatterers in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…The first peak, ( i ) the HP at ∼529 eV (blue), is situated at lower binding energies compared to ( ii ) the UHB peak at ∼530 eV (red), and ( iii ) a shoulder of the main edge onset at 533.0 eV (turquoise). The results of this analysis are visually compelling and illustrate the efficiency of spectral-weight transfer from the UHB to the HP, which is located at lower binding energies. ,, In subsequent analyses, we aim to further dissect the interfacial area and examine the evolution of holes, Sr content, and oxygen-vacancy formation at the atomic scale.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The first peak, ( i ) the HP at ∼529 eV (blue), is situated at lower binding energies compared to ( ii ) the UHB peak at ∼530 eV (red), and ( iii ) a shoulder of the main edge onset at 533.0 eV (turquoise). The results of this analysis are visually compelling and illustrate the efficiency of spectral-weight transfer from the UHB to the HP, which is located at lower binding energies. ,, In subsequent analyses, we aim to further dissect the interfacial area and examine the evolution of holes, Sr content, and oxygen-vacancy formation at the atomic scale.…”
Section: Resultsmentioning
confidence: 90%
“…In our work, we will address this emerging O-K edge prepeak as hole peak (HP). Chemical doping, such as Sr doping in LCO, shifts spectral weight from the upper Hubbard band (UHB) to the HP, thereby introducing holes into the system. Polarization-dependent XAS provides information on orbital occupation through high energy resolution, ,, but with limited spatial resolution, which is inevitable for characterizing innovative applications like Josephson junctions . EELS bridges this gap, offering atomic-scale characterization of orbital occupation, and the ability to quantify cations and anions, and their physical properties as a function of position by probing different phases.…”
mentioning
confidence: 99%
“…2 for the apical but not for planar O vacancies would be a key signature to look for with XPS. Notably, recent O K-edge x-ray absorption (XAS) experiments on SCO/LCO superlattices [23] have shown that the reduction of the second hole peak in the unoccupied DOS of SCO provides a signature of apical oxygen vacancies in SCO. In fact, earlier XAS measurements on overdoped LSCO [24] and electron energy-loss spectroscopy on SCO [25] have determined that such peaks belong to the apical oxygen unoccupied partial DOS.…”
Section: Resultsmentioning
confidence: 99%
“…2 for the apical but not for planar O vacancies would be a key signature to look for with XPS. Notably, recent O K-edge x-ray absorption (XAS) experiments on SCO/LCO superlattices 23 have shown that the reduction of the second hole peak in the unoccupied DOS of SCO provides a signature of apical oxygen vacancies in SCO. In fact, earlier XAS measurements on overdoped LSCO 24 and electron energy-loss spectroscopy on SCO 25 have determined that such peaks belong to the apical oxygen unoccupied partial DOS.…”
Section: Resultsmentioning
confidence: 99%